Design and Research of Control Rod Scheme for 10 MW Multifunctional Pool-type Research Reactor - HAN Peng, CHEN Xiaoliang, ZHANG Zhenyang, ZHU Jiachen, JIN Xiao (Yuanzineng kexue jishu)
Swimming pool-type reactors have typical advantages such as simple system, high inherent safety, powerful irradiation application function, moderate core size, diverse irradiation channels, and simple operation and maintenance. Among them, Class Ⅱ research reactors have low operating costs and can carry out various low-temperature irradiation tests. Their performance indicators are sufficient to meet the needs of fuel and material testing, production of various medical isotopes, and large-size single crystal silicon doping. They are an indispensable part of my country’s research reactors to achieve high, medium and low power matching. In order to meet the future needs of new reactor fuels, material tests and various neutron applications in my country, an overall design scheme for a new 10 MW multifunctional pool-type research reactor was proposed. At the same time, application facilities such as boron neutron capture therapy (BNCT), large-size single crystal silicon neutron transmutation doping (NTD) channels, horizontal channels and hot columns were set up in the reactor pool area to realize multifunctional neutron application capabilities. Aiming at the core design characteristics of low power, small number of fuel assemblies and anti-neutron well type, the influence of three different forms of control rods and their arrangements on the value of the rods themselves and the core was explored. Taking into account the safety of reactor operation, channel neutron fluence rate, power peak factor and subsequent fuel management methods, the forked control rod form was finally determined. The neutron fluence rate and linear power density in the forked control rod were analyzed to ensure its safety in use. The results show that for each core scheme using forked control rods, the maximum full-power operation days are lower, but the power distribution of the fuel assembly is flat, and the total power peak factor is ＜1.5. Compared with other schemes, the average thermal neutron fluence rate in the core channels is higher throughout the life cycle. Considering the safety performance of the control rods, the maximum temperature of the inner control plate is also far below its temperature limit. By comparing three types of control rods, this paper reveals the typical characteristics of three mature control rod schemes suitable for compact cores and plate-shaped fuel assemblies, and proposes a design scheme for a control system for a 10 MW multifunctional pool-type research reactor using forked control rods, which makes the reactor power peak factor lower and the channel neutron fluence rate higher, ensuring stable and safe operation of the core and ensuring that the research reactor has efficient irradiation capability.